RAS and RAF signaling in melanoma: biology and therapies - Marais, Richard (Henry Stewart Talks, 2010)
Melanoma, BRAF and RAS mutated in approximately 70% of cases, Mouse models of melanoma, Oncogenic BRAF can be a founder mutation in melanoma, Mouse models replicate human disease, BRAF inhibitors induce paradoxical activation of CRAF and drive pathway activation, Kinase-dead BRAF mimics this and potentiates RAS ooncogenesis, BRAF inhibitors induce excellent responses in patients, but may induce mechanism-based side effects through CRAF